2011
DOI: 10.3402/qhw.v6i1.5296
|View full text |Cite
|
Sign up to set email alerts
|

“They can do whatever they want”: Meanings of receiving psychiatric care based on a common staff approach

Abstract: This study deepens our understanding of how patients, when cared for in a psychiatric ward, experience situations that involve being handled according to a common staff approach. Interviews with nine former psychiatric in-patients were analyzed using a phenomenological–hermeneutic method to illuminate the lived experience of receiving care based on a common staff approach. The results revealed several meanings: discovering that you are as subjected to a common staff approach, becoming aware that no one cares, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This evoked feelings of disrespect, humiliation, abandonment, and of being denied the opportunity for dialogue. However, the absence of a common staff approach could evoke feelings of disappointment and unsafety (Alexander, 2006;Enarsson et al, 2011). When routines and rules are understandable, adapted to individual needs, and used consistently and equally among patients they offer safety (Lindgren et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This evoked feelings of disrespect, humiliation, abandonment, and of being denied the opportunity for dialogue. However, the absence of a common staff approach could evoke feelings of disappointment and unsafety (Alexander, 2006;Enarsson et al, 2011). When routines and rules are understandable, adapted to individual needs, and used consistently and equally among patients they offer safety (Lindgren et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Rules of the ward can create conflicts if they are difficult to understand, are rigid and their application is perceived as arbitrary [26, 32, 33]. Patients may perceive that they have to adapt to the ward environment, have days without meaningful activities and accept changes in medication without being consulted [22, 27, 32, 3436]. They may perceive that if they do not adapt, or show negative emotions, they might be subjected to coercive measures or be frightened by staff into adapting [22, 3133].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 This method has been used previously to explore ethical standpoints held by nursing staff in relation to forced feeding 19 and the use of physical restraints. 20 The vignette, based on knowledge obtained in earlier studies of the common staff approach, [3][4][5] was constructed to elicit the interviewees' personal ethical reasoning in a hypothetical case of a common approach used to restrict smoking in a psychiatric in-patient. The interviewees were aware of the aim of the vignette and of the study.…”
Section: Data Collectionmentioning
confidence: 99%
“…15 Earlier studies of a common staff approach in psychiatric care have shown that ethical questions and conflicts between ethical perspectives arise when carers have to choose whether to be loyal to their colleagues or to the patient. [3][4][5] However, although nurse-initiated rules in psychiatric care have been investigated 16 no study to our knowledge has aimed explicitly to investigate the common staff approach from an ethical perspective. Psychiatric patients are in a vulnerable situation when being cared for; often not being able to control their personal milieu when admitted to a psychiatric ward.…”
Section: Introductionmentioning
confidence: 99%